Factors related to the patient safety climate in an emergency hospital - Dayse Edwiges Carvalho Castilho; Ana Elisa Bauer de Camargo Silva; Fernanda Raphael Escobar Gimenes; Ranielle de Lima Silva Nunes; Ana Claudia Andrade Cordeiro Pires; Cristina Alves Bernardes
Objective: to verify the relationship between the socio-demographic and work profile of the nursing professionals and the patient safety climate in a public emergency hospital. Method: a cross-sectional study carried out with 177 nursing professionals from a public emergency hospital. For data collection, the Safety Attitudes Questionnaire - Short Form 2006 was used, validated and cross-culturally adapted to the Portuguese language. To check the factors related to the instrument's domains, bivariate and multivariate analyses were performed. Results: working in the medical and surgical clinic or emergency room, on a night shift, and having the intention to leave nursing, reduced the general safety climate in the multiple regression analysis. The younger professionals, with less than four years in the institution, and those who worked in the night shift had a lower safety climate related to the perception of the management. On the other hand, having a work contract with a hired worker improved the general safety climate and workplace satisfaction. Conclusion: identifying predictors on patient safety scores is an important management tool that allows diagnosing, planning and executing activities from the domains that need to be improved.